Trials and Tribulations at Chiyoda: A short overview of Japan’s current situation in the International arena (2019)
With the beginning of the Reiwa era in May 2019, the high complexity of Japan's relations with its neighbors has become a matter of consideration. Most of these relationships are highly intricate, driven by intense and pragmatic economic exchanges amid disputes over past aggressions and territorial demarcations. This leads to a state that has made waiver of war a pillar of its post-war consensus, must find a way to strengthen its capabilities and question how and why it will use force. Japan has the need to intensify its exchanges with its neighborhood and with other regions, in order to support broader economic reforms and support the most important social changes.